Polycapillary-based 3D X-ray imaging of porous organic materials; Journal of Instrumentation; Vol. 13 : International Congress on X-ray Optics and Microanalysis (ICXOM24) - Cherepennikov Yu. M. Yuriy Mihaylovich; Hampai D. Darjyush; Azzutti C. Claudia; Krasnykh A. A. Angelina Aleksandrovna; Miloichikova I. A. Irina Alekseevna; Stuchebrov S. G. Sergey Gennadevich; Batranin A. V. Andrey Viktorovich; Dabagov S. B. Sultan Barasbievich (2018, 2018)
Title screen